KOMUNIKASI INTERPERSONAL PEKERJAAN SOSIAL TERHADAP LANSIA - Noviana Aini (MIYAH : Jurnal Studi Islam, 2016)
Abstract: This paper seeks to analyze how social work can utilize communication aspect as a skill for social work practices and how social worker practice their communication with elderly people. Every people who live with elderly have a stigma if communicate with elderly is troublesome. So, to answer that, this paper deals particularly with the four issues as follows: (1) the problem between social work and elderly people; (2) the concept skill of social work interpersonal communication toward social work practices with elderly; (3) elderly people, and their need in live; (4) the connection between social work and communication; (5) the verbal and non verbal in interpersonal communication that should be done by social worker to serve elderly people. The paper focuses its analysis on the interpersonal social work communcation and its connected in communication. The basic argument developed throughout this paper is that social worker can utilize communication aspect for their practices during intervention and assessment process. My paper also use some Koran’s verses to view how is a social worker should’ve be a good proffesional worker. Keywords: Social work, Interpersonal communication, Elderly people.